Fasting Imparts a Switch to Alternative Daily Pathways in Liver and Muscle - Kinouchi, Kenichiro; Magnan, Christophe; Ceglia, Nicholas; Liu, Yu; Cervantes, Marlene; Pastore, Nunzia; Huynh, Tuong; Ballabio, Andrea; Baldi, Pierre; Masri, Selma; Sassone-Corsi, Paolo (Cell reports (Cambridge), 2018)
The circadian clock operates as intrinsic time-keeping machinery to preserve homeostasis in response to the changing environment. While food is a known zeitgeber for clocks in peripheral tissues, it remains unclear how lack of food influences clock function. We demonstrate that the transcriptional response to fasting operates through molecular mechanisms that are distinct from time-restricted feeding regimens. First, fasting affects core clock genes and proteins, resulting in blunted rhythmicity of BMAL1 and REV-ERBα both in liver and skeletal muscle. Second, fasting induces a switch in temporal gene expression through dedicated fasting-sensitive transcription factors such as GR, CREB, FOXO, TFEB, and PPARs. Third, the rhythmic genomic response to fasting is sustainable by prolonged fasting and reversible by refeeding. Thus, fasting imposes specialized dynamics of transcriptional coordination between the clock and nutrient-sensitive pathways, thereby achieving a switch to fasting-specific temporal gene regulation. [Display omitted] •Transcriptional response to fasting is robustly rhythmic in liver and muscle•Lack of food fails to sustain “free-running” conditions of peripheral circadian clocks•Genes are temporally regulated by the clock and fasting-related transcription factors•Rhythmic response to fasting is reversible by refeeding Kinouchi et al. reveal that fasting affects peripheral circadian clocks in the liver and skeletal muscle. Fasting operates by influencing the circadian clock and fasting-sensitive transcription factors, thereby cooperatively achieving fasting-specific temporal gene regulation.